دراسة ستراتغرافية و بترولوجية للتشكيلات الكريتاسية في منطقة جبل الزاوية-سورية (Latakia University Journal -Basic Sciences Series, 2018)
اهتم هذا البحث بدراسة التشكيلات الكريتاسية في مواقع تكشفها كافة في منطقة جبل الزاوية في سورية. و نفّذ بالاعتماد على الدراسات الحقلية المفصَلة لأربعة مقاطع جيولوجية تغطي المنطقة بأكملها، و على الدراسات المخبرية المستحاثية و الفلزية و الكيميائية و المجهرية المعمّقة . سمحت هذه الدراسات متكاملة بتحديد الوضع الستراتغرافي و الترسيبي للمنطقة. فمن الناحية الستراتغرافية تم وضع الحدود الفاصلة بين العصور و الطوابق الكريتاسية المختلفة وتوصيف كلٍ منها وتحديد محتواها المستحاثي المميِز.كما تمت الإشارة إلى وجود طابق الألبي لأول مرة في منطقة الدراسة. و من الناحية الترسيبية، تم تقسيم التشكيلات المدروسة إلى سبع وحدات ليثوستراتغرافية متباينة ، و تقديم وصف بترولوجي متكامل لكل منها ضمن مفاهيم الدورات و المتواليات الرسوبية. تعّد هذه الدراسة قاعدة لاستنباط الشروط وتحديد البيئات المسؤولة عن الترسيب، و استنتاج التطور الباليوجغرافي العام للمنطقة.كما تشكل منطلقاً للإستفادة من صخور هذه المنطقة و تحديد محتواها من المواد المفيدة و توجيه أعمال استثمارها . This research was interested in studying Cretaceous Formations in sites of its appearance in the region of Al-zawiyeh mountain in Syria. It was performed depending on detailed field studies of four geological sections covering the whole region,and on deep laboratory, paleontological, mineral, chemical and microscopically studies. These all studies together allowed to specify stratigraphical and sedimentary attitude of the region . From the stratigraphical side, limits separating the different Cretaceous periods and stages were established, and was described individually and its distinctive paleontological content was determined. Albian stage was first called at the region of the study. From the sedimentary side, studied formations was divided into seven different lithostratigraphical units introduced to each of them within the sedimentary concepts of sequences and cycles. This study is considered a fundament to conclude conditions and to specify the environments responsible for sedimentation, and to deduce general Paleogeo- graphical growth of the region. It also forms a beginning to take advantage of the rocks of this region and to determine its content of beneficial materials and to direct its investment.